Listening to further education students' perspectives: examining student voice practice through the lens of auto-driven photo elicitation. Issue 4 (2nd October 2021) - Homer, Damien
ABSTRACT: This study explores student voice practice from a student's viewpoint. Within England, United Kingdom (UK) student voice initiatives can manifest themselves in many ways, for example: surveys, councils, governors, representative groups, committees and student bodies such as the National Union of Students. The young people that took part in this study were between 16 and 20 years old. In total, 57 students took part in the research: 22 females and 35 males. The students were from a variety of socio-economic backgrounds. The setting was a Further Education College in an urban area of Central England, which serves students from areas of social and economic disadvantage. The project employed a mixed methods research design, with Bourdieu's notions of social capital applied to the analysis. Students took part in focus groups and auto-driven photo-elicitation, followed by semi-structured interviews. The data was analysed thematically utilising an interpretivist approach. The themes demonstrated a student body that was largely dismissive of formal channels of student voice practice, preferring different modes of interaction with their teachers. The findings have implications for student voice practice across England and offer insight into how young people may better be enabled to shape their educational experiences.